2014
DOI: 10.11607/jomi.2014suppl.g1.2
|View full text |Cite
|
Sign up to set email alerts
|

Computer Technology Applications in Surgical Implant Dentistry: A Systematic Review

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
392
6
23

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 468 publications
(534 citation statements)
references
References 59 publications
30
392
6
23
Order By: Relevance
“…Consequently, it is a general opinion that in vitro and cadaver studies may overestimate accuracy and underestimate error [22]. When considering in vivo studies, higher values in measurements confirmed the better outcomes as stated [25,26]. Computer-aided surgery has been advocated for clinical situations presenting a limited quantity of bone, frequently characterized by critical anatomical situations.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is a general opinion that in vitro and cadaver studies may overestimate accuracy and underestimate error [22]. When considering in vivo studies, higher values in measurements confirmed the better outcomes as stated [25,26]. Computer-aided surgery has been advocated for clinical situations presenting a limited quantity of bone, frequently characterized by critical anatomical situations.…”
Section: Introductionmentioning
confidence: 99%
“…This classification was chosen because of tooth support of the surgical guide, which provides better fit and reproducibility as opposed to mucosal or bony support of a surgical template. 7 In each model, the edentulous region consisted of the first and second premolar and the second molar, bilaterally (Fig. 1A).…”
Section: Sample Collectionmentioning
confidence: 99%
“…(Implant Dent 2016;25:222-226) Key Words: cone beam computed tomography, accuracy, guided surgery, dental implants transfer of the planning data, surgical template production, positioning the surgical guide, and implant insertion. 7 CBCT device selection plays an important role in determining the accuracy of guided surgery because different accuracy levels have been described for different CBCT devices. 8 One recent report described CBCT device selection to have a significant influence on the transfer accuracy of guided surgery.…”
mentioning
confidence: 99%
“…24 A recent systematic review concluded that computer-guided implant surgery provided a predictable level of accuracy. 25 With development of technology, 26 the Standard Tessellation Language (STL) files resulting from an intraoral digital diagnostic impression and computeraided design and computer-aided manufacturing (CAD/ CAM)-fabricated virtual diagnostic waxing and the Digital Imaging and Communications in Medicine (DICOM) files generated from CBCT scans can be merged in the virtual implant planning software to formulate a prosthetically driven implant surgical plan for subsequent computerguided implant surgery. 27,28 This process eliminates the need for a customized radiographic template and allows digital diagnostic impression and a CBCT scan to be completed in a single visit; implantation surgery can be performed during the patient's second visit.…”
mentioning
confidence: 99%